2006
DOI: 10.1086/507294
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With Antiseptic Hand Rub Use in Intensive Care Units The Hawthorne Effect

Abstract: The Hawthorne effect has a marked influence on compliance with AHR use, with a 55% increase of compliance with overt observation. This result is consistent throughout subgroups. The rate of compliance with AHR use may in fact be lower than we thought because of results from studies that did not take the Hawthorne effect into account. The results of this study underline the necessity for infection control teams to be on wards as often as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(148 citation statements)
references
References 12 publications
12
133
0
3
Order By: Relevance
“…Although our observers remained unobtrusive, we could not eliminate a Hawthorne effect, which has been shown to influence hand hygiene compliance. 37 We recognize that our hand hygiene compliance data may be inflated; we used a best-case scenario. Nevertheless, this method was applied consistently across the hospital by trained external observers and was useful to monitor trends over the course of the program.…”
Section: Discussionmentioning
confidence: 99%
“…Although our observers remained unobtrusive, we could not eliminate a Hawthorne effect, which has been shown to influence hand hygiene compliance. 37 We recognize that our hand hygiene compliance data may be inflated; we used a best-case scenario. Nevertheless, this method was applied consistently across the hospital by trained external observers and was useful to monitor trends over the course of the program.…”
Section: Discussionmentioning
confidence: 99%
“…This focus on hand hygiene has in turn contributed to increased awareness of the Hawthorne effect. One study reported a 55% increase in use of alcohol handrub when health workers were aware that they were being watched compared to when they were unaware 26 . Compliance declined from 61% when doctors knew they were being observed to 44% when they were unaware 27 while in another study 28 hand hygiene compliance was reported to increase in the presence of data collectors known to staff compared to data collection by someone they did not recognise.…”
Section: Behaviour Change During Hand Hygiene Observation: Historicalmentioning
confidence: 99%
“…The role of hand hygiene is crucial and has been recognized as the single most important preventive measure [161]. Nevertheless, compliance with hand hygiene procedures is often poor, at only 30%-40% [162][163][164][165]. Compliance seems to vary depending on several issues: women tend to comply more often than men, and nurses more often than physicians or nursing assistants [162,166].…”
Section: Hand Hygiene and Cross-transmissionmentioning
confidence: 99%
“…Hand hygiene compliance rates can be improved by educational campaigns [163,184,185]. The Hawthorne effect, first described in electric factory workers as early as in the 1930s [186], refers to the tendency of people under observation in a study context to behave differently from the way they otherwise do and may explain why the effect of educational campaigns could likely be short-lived [184].…”
Section: Hand Hygiene and Cross-transmissionmentioning
confidence: 99%
See 1 more Smart Citation